Introduction to Narrative Journalism - Wielechowski, Benjamin (Open textbook library., 2021)
This textbook was created for beginning narrative journalists exploring the craft. It is inspired by the Narrative Journalism course (JASS/COMP/ENGL 310) at the University of Michigan-Dearborn, and it is intended to be used as a guide and handbook. It is structured around the five elements of fiction, and provides both instruction and student examples of various narrative journalism projects.